PENGARUH PENGENDALIAN AKUNTANSI, KEJELASAN SASARAN ANGGARAN DAN SISTEM AKUNTANSI PEMERINTAH DAERAH TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MODERASI (Studi Kasus Organisasi Perangkat daerah Kabupaten Sukoharjo) - Ikhsand, Moch. Choirul (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
This research was“conducted to analyze effect of accounting control, targets clarity of budget and local government accounting“systems on the performance accountability of government agencies“by utilizing“information technology as a moderating variable in the regional“apparatus organization of Sukoharjo Regency. The“type of data used is quantitative data. The data source used is“primary data. The sampling technique was carried out using saturated sampling technique. The sample used was 44 respondents of regional apparatus organization employees. How to collect data by distributing questionnaires to employees of regional apparatus organizations in Sukoharjo Regency. Based on the test results from the study it can be concluded that accounting control has a significant effect, targets clarity of budget has a significant effect, and the“local government accounting system has a significant“effect on the performance accountability of Sukoharjo district government agencies. the use of information technology does not moderate accounting control, targets clarity of budget and local government accounting systems“on the accountability of performance of government agencies. “Future research is expected to extend the object of research and add other independent variables such as reporting systems, quality of internal control systems, decentralization and implementation of performance-based budgets, etc.